Rancang Bangun Aplikasi Perbandingan Algoritma Knuth-Morris-Pratt Dan Boyer Moore Pada Pencarian Katalog Buku - Ahmad Turmudi Zy; Zaky Ali Husaeni (Jurnal SIGMA, 2021)
The activities currently carried out in searching for book catalog data are less effective because the method used is still conventional. The string matching algorithm is a solution for making book catalog application search engines to be more accurate and faster when performing data searches. There are several string matching algorithms including the Knuth-Morris-Pratt and Boyer Moore algorithms which are the most effective in performing string matching in the case of book catalogs, for that we need a comparison analysis of the Knuth-Morris-Pratt and Boyer Moore algorithms using the Exponential Comparison Method to determine the algorithm. which are suitable. From the results of the comparisons made, it can be concluded that the Boyer Moore algorithm is faster and more accurate. Keywords: Application, Knuth-Morris-Pratt, Boyer Moore